Evaluating the effect of chlorpheniramine on patch test reactions amongst eczema patients sensitised to nickel - Shafinaz S,; Adawiyah Jamil,; Chan, LC; Norazirah MN, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Discontinuing antihistamines for patch testing (PT) in allergic contact dermatitis (ACD) is more conventional than evidence based. Data suggests that non-sedating antihistamines do not interfere with PT. Investigating the effects of sedating antihistamines are more relevant as these are recommended for eczema. We aimed to evaluate the effect of chlorpheniramine on PT, to determine the prevalence of nickel sensitization and common sensitizing allergens. An open labeled cohort study was conducted at two dermatology clinics. Patients indicated for PT underwent standard protocol where antihistamines were discontinued. Patients sensitised to nickel were subjected to a second nickel PT while taking chlorpheniramine. Results were evaluated using the North American Contact Dermatitis Research Group (NACDRG) score, a Mexameter measured erythema and pruritus was assessed using a visual analogue score. A total 82 patients were recruited, 28 (34.1%) were sensitised to nickel. The mean age was 40 ± 17.7 years with 22(26.8%) males and 60 (73.2%) females. Indications for PT included suspected ACD (57.3%), hand and feet eczema (34.1%) and severe eczema with suspected superimposed ACD (6.1%). The commonest sensitizing allergens were methyldibromoglutaronitrile (40.2%) nickel sulphate (34.1%), potassium dichromate (29.3%) and formaldehyde (24.4%). A second PT was performed on 23 patients. There was no difference in the NACDRG score with chlorpheniramine or without chlorpheniramine (p=0.968). Pruritus score was reduced by 1.39 ± 2.9, p=0.031 with chlorpheniramine. The degree of erythema was 611.46 ± 21.59 with chlorpheniramine versus 613.87 ± 27.5 without chlorpheniramine, p=0.671. Chlorpheniramine did not affect PT based on clinical and objective scorings. It has the additional benefit of reducing test-induced itch.